High diversity and local endemism in Aotearoa New Zealand's groundwater crustacean fauna - Fenwick, Graham D.; Greenwood, Michelle J.; Hogg, Ian D.; Meyer, Stacey J. (Ecology and evolution, 2021)
We used DNA barcoding to assess the diversity and distribution of New Zealand's groundwater amphipods and isopods (Crustacea) and to determine whether biodiversity and endemism within tectonically active New Zealand are similar to those of more tectonically stable continents. Sixty‐five wells were sampled in seven aquifers across four regions within the North and South islands of New Zealand, and resident invertebrates were morphologically identified and then assessed using sequencing of the mitochondrial DNA cytochrome c oxidase subunit one (COI) gene. Invertebrates were found in 54 wells. Of the 228 individual amphipods and isopods found in 36 of the wells, 154 individuals were successfully sequenced for COI (68% success rate) from 25 wells, with at least one well in each aquifer containing sequenced individuals. Of the 45 putative species identified using Barcode Index Numbers (BINs), 30 BINs (78% of all taxa and 83% of amphipods) were previously unrecorded. Substantial morphologically cryptic, species‐level diversity was revealed, particularly within the amphipod Family Paraleptamphopidae. Similarly, one isopod taxon morphologically identified as Cruregens fontanus was assigned to five well‐separated BINs based on COI sequences. Endemism appeared high, with all taxa regionally endemic; 87% of species were restricted to one aquifer and more than 50% restricted to one well. Non‐saturated species accumulation curves indicated that, while additional sampling may increase the range of some currently identified taxa, additional range‐restricted taxa are also likely to be discovered. Patterns of diversity and short‐range endemism were similar to those found elsewhere, including locations which are more tectonically stable. The predominance of local endemism within New Zealand's groundwater fauna suggests that land‐use activities and groundwater extraction require careful evaluation to minimize threats to groundwater biodiversity. We used DNA sequencing of the cytochrome c oxidase subunit one (COI) gene to examine the diversity and distribution of New Zealand's groundwater amphipods and isopods (Crustacea) and to compare diversity and endemism within tectonically active New Zealand relative to more tectonically stable continents. Endemism appeared high, with all taxa regionally endemic; 87% of species were restricted to one aquifer and more than 50% restricted to one well. Patterns of diversity and short‐range endemism were similar to those observed elsewhere, including more tectonically stable locations.